Pengaruh Manajemen Waktu dan Dukungan Sosial Terhadap Stres Akademik pada Mahasiswa Baru Universitas Islam Negeri Maulana Malik Ibrahim Malang - Qori'atun Nabila; Sri Ramadani (Lembaga Kajian, Penelitian dan Pengembangan Mahasiswa Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
First-year university students often face complex academic demands and significant adjustments to their new learning environment, making them vulnerable to academic stress. Difficulties in time management and limited social support frequently intensify this condition. This study aims to examine the influence of time management on academic stress, the influence of social support on academic stress, and the combined effect of both variables on first-year students at Universitas Islam Negeri Maulana Malik Ibrahim Malang. The study employed a quantitative approach with a correlational design and used multiple linear regression as the analytical technique. A total of 101 respondents were selected through random sampling. All research instruments were confirmed to be valid and reliable based on the appropriate statistical tests. The findings show that time management has a significant influence on reducing academic stress, and social support also contributes significantly to lowering students’ stress levels. Simultaneously, both variables account for 66.5% of the variance in academic stress. These results highlight that effective time management and adequate social support are essential factors that help first-year students adapt to academic demands and prevent excessive stress.